The Effectiveness of a Proposed Training Program to Develop Nonverbal Communication Skills in Children with Autism Spectrum Disorder - Mohammed, Asst.Prof.Dr. Nazanin Osman Mohammed; Hassan, Dr. Avan Abdullah Hassan (Sulaimani Journal for Humanities, 2025)
The study aimed to investigate the effectiveness of the proposed training program on developing nonverbal communication skills among a sample of (4) children with autism spectrum disorder, between (5-7) years of age, the one-group quasi-Experimental approach was used by conducting pre- and post-measurement of the sample, and equality was achieved among the group members through the application of the CARS scale for childhood autism (moderate autism). The researchers adopted Makansi’s nonverbal communication scale (2018), which consists of six dimensions: (visual communication, joint attention, imitation, use of signs, understand facial and body gestures, use of gesture, physical gestures, responding and executing commands). After verifying its validity and reliability, the proposed training program prepared by Makansi was applied due to its suitability to the current study. (SPSS) program was used to fulfil the statistical analyses of the data. The arithmetic means and standard deviations were calculated, as well as the Wilcoxon test, to prove the existence of a difference in the effectiveness of the proposed program in developing non-verbal communication skills among children with autism spectrum disorder (study sample) and between its various dimensions, the findings approved the existence of statistically significant differences at the level of individual ranks among the study sample for the skills of : (Joint attention ,imitation, understanding facial and physical gestures, responding and executing commands), while the results showed that there were no statistically significant differences at the level of the ranks of the study sample members with respect to the skills: (visual communication, and use of signs). In the light of these results, the researchers suggested some recommendations and suggestions.
Keywords: nonverbal communication skills; autism spectrum disorder; training program